Slikanje z magnetno resonanco v diagnostiki sakroiliitisov iz skupine seronegativnih spondiloartritisov - Gardaševič, Ivana (Medicinski razgledi, 2000)
In early diagnosis of sacroiliitis as a part of seronegative spondyloarthritides, conventional radiography and computed tomography are used. Computed tomography was the most sensitive diagnostic method before discovering magnetic resonance imaging. It has been widely accepted that computed tomography is the radiological method of choice for detection of early subchondral cortical bone erosions. The ideal radiological technique should give the diagnosis before the occurrence of final erosions. The purposeof our study was to establish the role of magnetic resonance imaging with the resonantic contrast medium Gd-DTPA in early diagnosis of sacroiliitisin patients with suspected ankylosing spondylitis. In 25 patients with clinical diagnosis of suspected seronegative spondyloarthritis conventional radiography, computed tomography and magnetic resonance imaging were performed. In 10 patients no abnormalities were demonstrated. In 13 casescomputed tomography and magnetic resonance imaging revealed sacroiliitis.In 2 patients with normal plain films and computed tomographs were para- and intraarticular changes of signal intensity in the magnetic resonance images compatible with sacroiliitis. The results of our study suggest that magnetic resonance imaging can be considered as an important modalitiy for early diagnosis of seronegative spondyloarthritides.
Keywords: revmatična obolenja; Spondylitis; Radiography; spondilitis; Sacroiliac joint; Magnetic resonance imaging; Tomography, x-ray computed; Gadolinium; Dtpa; Spondylitis, ankylosing; diagnostika